2021
DOI: 10.21203/rs.3.rs-278757/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delirium In ICU Patients With Malignancy: Patient Characteristics, Resource Utilization and Outcomes

Abstract: Background: Whereas delirium in the general intensive care unit (ICU) population is common and well studied, knowledge on ICU delirium in patients with malignancy is scarce. The aim was to assess the frequency of delirium and its impact on resource utilizations and outcomes in ICU patients with malignancy.Methods: This retrospective, single-center longitudinal cohort study included all patients with malignancy admitted to ICUs of a University Hospital during one year. Delirium was diagnosed by an Intensive Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Full texts of these studies were retrieved and reviewed for inclusion. Finally, 24 potentially eligible studies were excluded 9,27‐49 , leaving 17 studies for inclusion (Appendix B). Table 1 provides an overview of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Full texts of these studies were retrieved and reviewed for inclusion. Finally, 24 potentially eligible studies were excluded 9,27‐49 , leaving 17 studies for inclusion (Appendix B). Table 1 provides an overview of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of delirium in patients diagnosed with cancer is high, although it varies depending on patient characteristics and the stage of cancer. 3,4,8 Delirium that is not diagnosed early and cannot be managed effectively is a factor that negatively affects the care and patient outcomes of cancer patients and increases the care burden. [7][8][9] There are many risk factors that cause delirium development.…”
Section: Discussionmentioning
confidence: 99%
“…3 In a study conducted by Sieber et al, delirium was observed in 36% of the patients with malignancy, and the incidence of delirium development was higher in patients with liver, lung, and colorectal malignancies, respectively. 4 It has been reported that this variance in the incidence of delirium differs according to the delirium assessment method used in studies, education of personnel, and the delirium subtype. 1,5,6 Hyperactive delirium is often associated with agitation and discomfort, and increased psychomotor activity makes delirium easily recognized.…”
Section: Oncology Nurses' Practices On Diagnosis Prevention and Manag...mentioning
confidence: 99%
See 2 more Smart Citations